Gene co-expression network analysis reveals positive effects of concentrate supplementation on energy metabolism in early-weaned Nellore calves - Russo, Gustavo Henrique; Tinoco, Gustavo Lucas Bezerra; Vicari, Marcelo Ricardo; Nogueira, Rebeca Soares; Melo, Paloma Leandra Garcia; Torrecilhas, Juliana Akamine; Curi, Rogério; Moriel, Philipe; Baldassini, Welder Angelo; Chardulo, Luis Artur Loyola; Pereira, Guilherme Luis (Frontiers in Animal Science, 2025)
IntroductionTo determine the impact of early weaning combined with concentrate supplementation on skeletal muscle energy metabolism, we profiled gene co-expression networks in Bos indicus (Nellore) calves.Material and methodsLongissimus thoracis biopsies were collected from eight calves per treatment (conventional and early weaning) at 120 and 205 days of age (longitudinal sampling). All calves grazed Brachiaria decumbens pasture until 120 days. Subsequently, early weaned calves received a 1% body weight concentrate supplement (20% CP, 75% TDN) post-weaning. Total RNA was extracted, and 32 mRNA libraries were generated for RNA sequencing. Using normalized count matrix, we constructed gene co-expression modules using webCEMiTool and performed over-representation analysis (ORA) for pathway enrichment (KEGG). Additionally, we used Gene Set Enrichment Analysis (GSEA) to evaluate the regulatory activity (up- or downregulation) of identified gene modules.ResultsResults: Modules associated with pathways such as insulin signaling, unsaturated fatty acid biosynthesis, and PPAR signaling showed a significantly higher proportion of upregulated genes. Key hub genes within these early weaning-related modules were linked to lipid synthesis and adipocyte differentiation. Thus, early weaning followed by concentrate supplementation modified the gene expression profile, enhancing pathways involved in energy metabolism, adipogenesis, lipogenesis, and lipolysis inhibition.DiscussionThese findings suggest that early nutritional intervention can positively influence metabolic pathways associated with growth and body composition in Nellore calves. Despite the multifactorial nature of these traits and their susceptibility to modification during post-weaning phases, the current results demonstrate potential for long-term positive effects on carcass composition and final product quality.